Evidence for an anti-inflammatory loop centered on polymorphonuclear leukocyte formyl peptide receptor 2/lipoxin A4 receptor and operative in the inflamed microvasculature - Brancaleone, Vincenzo (2011)
The importance of proresolving mediators in the overall context of resolution of acute inflammation is accepted and prominent, though little is known on whether these anti-inflammatory and pro-resolving molecules act in concert. Here we focused on lipoxin A(4) (LXA(4)) and annexin A1 (AnxA1) since these two very different mediators converge on a single receptor, formyl peptide receptor type 2 (acronym FPR2/ALX). Addition of LXA(4) to human PMN provoked a concentration- and time-dependent mobilization of AnxA1 onto the plasma membrane, as determined by western blotting and flow cytometry analyses. This property was shared by another FPR2/ALX agonist, antiflammin-2 (AF2), and partly by fMLP or peptide Ac2-26 (an AnxA1 derivative which can activate all three members of the human FPR family). An FPR2/ALX antagonist blocked AnxA1 mobilization activated by LXA(4) and AF2. Analysis of PMN degranulation patterns and phospho-AnxA1 status suggested a model where the two FPR2/ALX agonists mobilize the cytosolic (and not the granular) pool of AnxA1 through an intermediate phosphorylation step. Intravital microscopy investigations of the inflamed mesenteric microvasculature of wild type and AnxA1(−/−) mice revealed that LXA(4) provoked leukocyte detachment from the post-capillary venule endothelium in the former (>50% within 10 min; P<0.05), but not the latter genotype (~15%; NS). Furthermore, recruitment of Gr1(+) cells into dorsal air pouches, inflamed with IL-1β, was significantly attenuated by LXA(4) in wild type, but not AnxA1(−/−) mice. Collectively, these data prompt us to propose the existence of an endogenous network in anti-inflammation centred on PMN AnxA1 and activated by selective FPR2/ALX agonists.